Community Participation in the Implementation of Simultaneous Regional Head Elections during the 2020 Covid-19 Pandemic in Banten Province - Dairul; Bahrullah Akbar; Aries Djaenuri; Sampara Lukman (International Journal of Science and Society, 2021)
In terms of community involvement, the conduct of regional head elections embodies the representational function inherent in popular sovereignty. The role of representation is one of the government's functions. As a result, the selection represents the aim of Government Science. The purpose of this research is to assess "Community Participation in the Conduct of Simultaneous Regional Head Elections during the Covid-19 Pandemic Period" in Banten Province (Case Study: Serang Regency, Pandeglang Regency, Cilegon City, and Tangerang City) in 2020. This study employs a qualitative research design in conjunction with a descriptive research method. The analysis used in this study is political participation from The International Encyclopedia of the Social Sciences. A conceptual definition is developed that Community Participation in Simultaneous Regional Head Elections is the active participation of voters in various voter participation levels in the 2015 simultaneous Regional Head Elections (Pilkada). 2020 in Banten Province, voter turnout will exceed 60% in the four regencies/cities hosting simultaneous regional elections on December 9 2020. Pandeglang Regency achieved 68.7 per cent in 2020, up from 56 per cent in 2015, Cilegon City achieved 79.79 per cent in 2020, exceeding the national target by as much as 63.51 per cent in 2015, Serang Regency earned 63.3 per cent in 2020, up from 50.8 per cent in 2015 Pilkada. South Tangerang City achieved 60.4 per cent in 2020. In 2015, voting turnout was 57 per cent, a considerable rise despite the current epidemic of Covid-19.